Isolated Congenital Absence of Lumbosacral Facet Joint - Joseph Maalouly; Dany Aouad; Hicham G. Abd El Nour; Alexandre Nehme; Fouad Jabbour (Case Reports in Orthopedics)
A congenital absence of the lumbar facet joint is a rare reported condition. This is the case of a 32-year-old male patient presenting with severe low back pain radiating to his right lower limb. Physical examination revealed no motor deficits, but right lower limb numbness was reported over dorsum aspect of the right foot. No other sensory or motor disturbances were reported or found on exam. Imaging studies, consisting of a spine MRI and spine CT scan with 3D reconstruction, revealed the absence of the right L5-S1 zygapophyseal joint. The patient was treated conservatively with resolution of his symptoms on one-month follow-up.